Prevalence of multiple morbidities and cancers in individuals with Down syndrome: A matched descriptive study using linked electronic health record data - Caoimhe McKenna; Kabir Yoshinori Khanna; Meghan A. Cupp; Darlington David Faijue; Anne G.M. Schilder; Arturo Gonzalez-Izquierdo; Muhammad Qummer ul Arfeen; Andre Strydom; Dougal Hargreaves; Rachel Xue Ning Lee; Monica Lakhanpaul; Logan Manikam (PLoS ONE, 2026)
Background Down syndrome is associated with the development of multiple morbidities throughout the life course, yet comprehensive data on its relative burden remains limited. This descriptive, matched, retrospective cohort study aimed to assess the 20-year period prevalence of morbidities and cancers in adults and children with Down syndrome. Methods We analysed electronic health record data from January 1998 to December 2017, matching individuals with Down syndrome to up to five matched controls. Period prevalence and odds ratios (OR) were calculated for 30 morbidities and 24 cancers. Results This study included 4,648 individuals with Down syndrome (32,920 person-years) and 23,238 matched controls (236,883 person-years). Most morbidities had a significantly higher period prevalence in individuals with Down syndrome, including hypothyroidism (30.4%), congenital cardiac disease (27.8%), and epilepsy (21.9%). We found an increased comparative risk of autism (OR 7.5, 95% CI 6.4–8.0), chronic kidney disease (OR 2.4, 95% CI 2.1–2.8) and inflammatory bowel disease (OR 2.5, 95% CI 2.2–2.8). Individuals with Down syndrome also had a significantly higher period prevalence of leukaemia and testicular cancer. Conversely, most solid tumours were less prevalent in individuals with Down syndrome. Conclusions This study presents findings from one of the largest described cohorts of individuals with Down syndrome, contributing to an understanding of the comparative prevalence of multiple comorbidities and cancers among both adults and children with Down syndrome. These findings support prioritising surveillance for a range of conditions such as hypothyroidism and childhood leukaemia and may justify de-emphasising routine screening for several solid tumours in Down syndrome.